Cover Picture: A Dinuclear Cobalt Cryptate as a Homogeneous Photocatalyst for Highly Selective and Efficient Visible‐Light Driven CO2 Reduction to CO in CH3CN/H2O Solution (Angew. Chem. Int. Ed. 3/2017). Issue 3 (21st December 2016) - Ouyang, Ting; Huang, Hai‐Hua; Wang, Jia‐Wei; Zhong, Di‐Chang; Lu, Tong‐Bu
Abstract : Synergistic catalytic effects aid the photocatalytic reduction of CO2 to CO by a dinuclear cobalt cryptate complex in CH3 CN/H2 O solution. In their Communication on page 738 ff., D. C. Zhong, T. B. Lu, and co‐workers demonstrate that one Co II unit serves as a catalytic center and the other Co II unit acts as an assistant catalytic site to facilitate the cleavage of the C−O bond of the O=C−OH intermediate, thus leading to a higher catalytic activity than for the corresponding mononuclear Co II complex.